The effects of pulmonary hypertension on skeletal muscle oxygen pressures in contracting rat spinotrapezius muscle. Issue 10 (17th September 2021) - Schulze, Kiana M.; Weber, Ramona E.; Colburn, Trenton D.; Horn, Andrew G.; Ade, Carl J.; Hsu, Wei‐Wen; Poole, David C.; Musch, Timothy I.
Abstract : New Findings: What is the central question of this study? Does impairment in the dynamics of O2 transport in skeletal muscle during a series of contractions constitute a potential mechanism underlying reduced exercise capacity in pulmonary hypertension? What is the main finding and its importance? Pulmonary hypertension compromises the dynamic matching of skeletal muscle O2 delivery‐to‐utilization following contraction onset in the rat spinotrapezius muscle. These results implicate a role for vascular dysfunction in the slow V ̇ O 2 kinetics and exercise intolerance present in pulmonary hypertension. Abstract: Pulmonary hypertension (PH) is characterized by pulmonary vascular dysfunction and exercise intolerance due, in part, to compromised pulmonary and cardiac function. We tested the hypothesis that there are peripheral (i.e., skeletal muscle) aberrations in O2 delivery ( Q ̇ O 2 )‐to‐O2 utilization ( V ̇ O 2 ) matching and vascular control that might help to explain poor exercise tolerance in PH. Furthermore, we investigated the peripheral effects of nitric oxide (NO) in attenuating these decrements. Male Sprague–Dawley rats ( n = 21) were administered monocrotaline (MCT; 50 mg/kg, i.p. ) to induce PH. Disease progression was monitored via echocardiography. Phosphorescence quenching determined the O2 partial pressure in the interstitial space ( P O 2 is ) in the spinotrapezius muscle at rest and during contractions under control (SNP−) and NO‐donor (sodium nitroprusside, SNP + ) conditions. MCT rats displayed right ventricular (RV) hypertrophy (right ventricle/(left ventricle + septum): 0.44 (0.13) vs. 0.28 (0.05)), pulmonary congestion, increased RV systolic pressure (48 (18) vs. 20 (8) mmHg) and arterial hypoxaemia ( P a O 2 : 64 (9) vs. 82 (9) mmHg) compared to healthy controls (HC) ( P < 0.05). P O 2 is was significantly lower in MCT rats during the first 30 s of SNP− contractions. SNP superfusion elevated P O 2 is in both groups; however, MCT rats demonstrated a lower P O 2 is throughout SNP+ contractions versus HC ( P < 0.05). Thus, for small muscle mass exercise in MCT rats, muscle oxygenation is impaired across the rest‐to‐contractions transition and exogenous NO does not raise the Q ̇ O 2 ‐to‐ V ̇ O 2 ratio in contracting muscle to the same levels as HC. These data support muscle Q ̇ O 2 ‐to‐ V ̇ O 2 mismatch as a potential contributor to slow V ̇ O 2 kinetics and therefore exercise intolerance in PH and suggest peripheral vascular dysfunction or remodelling as a possible mechanism.